Socio-economic stability of people through social development projects with special focus on rural areas of Sindh: a vision for prosperity - Santosh Kumar; Chandan Lal Rohra; Kanya Lal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
It is unavoidable fact that our country is blessed with immeasurable natural resources but only there is dire need of proper utilization of those resources. It is a matter of great grievance that our matchless natural resources are being squandered owing to lack of expert strategies. If proper planning and special focus is paid towards the social development of rural areas it would not be big boast to claim that the fate of poverty stricken people living in the rural areas can be changed within finger tips. There have been best precedents in our country in the socio-economic stability of people whenever social and economic projects have been launched to address the poverty of people living in backwards areas of Pakistan. This present research intends to amylase the positive impact of social and economic projects on the social well-being of people through economic generation opportunities. SPSS software has been applied to verify the obtained data collected from rural areas. Chi-square test obtained through SPSS is greater with P-value 0.000 which indicates that our obtained data is valid and socio-economic stability of people is greatly boosted through social development projects if implemented through well-planned manner. The present research will help the engineers and technician regarding the effect utilization of social development projects.
Keywords: 330; rural areas; social well-being; social development projects; poverty